Pengaruh Pemberian Berbagai Variasi Ukuran Tandan Kosong Kelapa Sawit pada Lahan Basah Buatan untuk Pengelolaan Air Asam Tambang - Pancar Delima; Bambang Joko Priatmadi; Akhmad Rizalli Saidy (Agroekotek View, 2020)
Acid mine drainage (AMD) is resulting from the exposure of rock containing ferrous of ferric sulfide mineral to rainwater and oxygen result in the generation of AMD. AMD characterized by highly acidic pH water with pH range ≤ 5 and containing heavy metals (Fe, Mn, Al) with high concentration. Therefore, AMD must be treated to ensure safety and minimize the environmental risk in order to request from the Ministry of  Environmental Readmitted Number 113 the Year 2003. The solution is using a passive treatment method with constructed wetland technology. Empty oil palm fruit having nutritive content with high relativity like N, P, K and if it is composted having pH value till 8 so that is potential to improve soil and water acidity. This research is to know the effect of giving variations measurement of empty oil palm fruit to constructed wetland technology for acid mine drainage management to fit the value of quality standard liquid wasted coal. This study using a randomized block design consisting of a single factor with 6 treatments and 3 replicants. Research has shown that giving various measurements of empty oil palm fruit has a real impact to increase the pH value, and decreasing Mn at AMD, but has no real impact on decreasing Fe (Fe2+) value.